Analisis Forensik Pada Instagram dan Tik Tok Dalam Mendapatkan Bukti Digital Dengan Menggunakan Metode NIST 800-86 - Ali Diko Putra, Muhammad; Wirawan Muhammad, Arif; Parga Zen, Bita; Yunita Kisworini, Rianti; Rohayati, Tuti (Jurnal Sistem Informasi Galuh, 2024)
Crime is currently increasing with the development of this smartphone, one of which is the crime of using social media. Instagram and Tik Tok are one of the most widely used social media applications in this era. The more users of this social media, it does not rule out the emergence of crimes against fellow users of this social media. Every activity carried out on social media, including criminal acts, leaves evidence or digital traces; whether deleted or not, all will be visible. Digital forensics is the study of how to obtain digital evidence obtained from digital devices. This study aims to determine the process of finding digital evidence on Instagram and Tik Tok social media applications that are accessed via smartphones using the National Institute of Standards and Technology (NIST) method. The stages in this digital forensic method include Collection, Examination, Analysis, and Reporting to obtain digital evidence on Instagram and TikTok using tools in the form of third-party software, namely MOBILedit Forensic Express, Autopsy, and FTK Imager tools. With the final result for the Instagram application tools, MOBILedit Forensic Express is able to acquire evidence with a percentage of 0.02%, for autopsy tools at 40%, and FTK Imager with a percentage of 57%. In the Tiktok application itself, MOBILedit Forensic Express gets a percentage of 27%, while an autopsy is 29%, and the last is the FTK Imager tool with a percentage of 71%. In this study, the FTK Imager tool is superior in the acquisition of evidence between the two tools.